Adherence to Vitamin D Supplementation during Infancy-A Single Pediatric Primary Practice Retrospective Study - Jerko Vucak; Jeronim Matijevic; Ivan Pivac; Josko Markic (MDPI AG, 2023)
The risk of vitamin D deficiency is high in infants. Therefore, potential vitamin D deficiency should be prophylactically treated with vitamin D supplementation. Achieving good adherence to recommended prophylactic regimens is the goal of every primary pediatrician. The aim of this paper was to establish whether Croatian infants receive recommended prophylactic doses of vitamin D regularly. We analyzed the prescription rate of vitamin D preparation during the first year of life in one pediatric primary practice. Our research has shown, for the first time in Croatia, that there is low treatment adherence. Only 7.6% of infants received the recommended doses of vitamin D. The percentage of infants in the moderately irregular adherence group was 19.3%. There was no statistical difference regarding urban or rural place of living or parents' educational level. Based on these findings, a comprehensive public health campaign is needed to improve adherence to vitamin D supplementation during infancy. Also, further studies on larger samples and on a national level are warranted.